Factors affecting morbidity and mortality in peptic ulcer perforation - Byakodi, Kadasiddeshwara G.; B. S., Harini; Teggimani, Vasant; Kabade, Narayan; Hiregoudar, Abhijit; M. R., Vishwas (International Surgery Journal, 2018)
Background: Peptic ulcer disease is very common disease in developing countries and so are its complications. With the introduction of H2 receptor antagonists and proton pump inhibitors, the incidence of elective surgery for peptic ulcer (PU) disease has decreased dramatically, although complications of peptic ulcer disease such as perforation and bleeding have remained fairly constant. Methods: A prospective study was conducted on43 patients presenting to KIMS Hospital, Hubli with features suggestive of hollow viscus perforation and intraoperative findings suggestive of peptic ulcer perforation from January 2015 to June 2016. Results: In this study, there were 43 cases of peptic ulcer perforation. Peptic ulcer perforation was common in third decade of life(n=12) with the mean age(SD) 39.88 years. Perforation is more common in males as compared to the female population 7.6:1. Post-operative morbidity is seen in 31 (72.1%) of patients and mortality in 4 (9.3%). Smoking, Alcohol beverage consumption, regular ingestion of NSAIDs were commonly seen in patients with peptic ulcer perforation but these factors were not significant risk factors for postoperative mortality and morbidity. Age ≥60 years (p-value 0.051), Female gender (p-value 0.012), Presence of co-morbid conditions (p-value 0.055), Shock on admission (p-value 0.029, perforation-surgery interval >24 hours (p-value 0.001), preoperative higher-grade ASA, purulent intraperitoneal collection (p-value 0.002) were statistically significant predictors of mortality. Conclusions: Perforated peptic ulcer (PPU) is a life-threatening disease with historically reported high morbidity and mortality rates. Age ≥60 years, female gender, presence of co-morbidities, preoperative shock, higher ASA grade, perforation-surgery interval >24 hours, Purulent intraperitoneal collection are inter-related statistically significant predictors of mortality. Therefore, proper resuscitation from shock, improving ASA grade and decreasing delay in surgery is needed to improve overall results.